Influence of diets supplemented with vitamins C and E on pirarucu (Arapaima gigas) blood parameters - Andrade, Jaqueline Inês Alves de (Comparative Biochemistry and Physiology - A Molecular and Integrative Physiology, 2020)
This study evaluated the influence of diets supplemented with 500, 800, 1200 mg kg- 1 of vitamin C (ascorbic acid or AA) and vitamin E (α-tocopherol or α-T) on the physiological responses of pirarucu fed for 2 months. Weight and mortality were not affected by dietary vitamin type or their concentrations. Significant increase (p < 0.05) on the red blood cells count was obtained on treatments with 800 and 1200 mg AA kg- 1 and on the hemoglobin concentration on treatment with 500 mg α-T kg- 1 relatively to control. Mean corpuscular volume presented a significant decrease (p < 0.05) on treatment with 800 and 1200 mg AA kg-1 when compared to control. Mean corpuscular hemoglobin concentration was significantly high (p < 0.05) on treatment with 500 mg α-T kg- 1. Only in vitamin C treatments, we noticed a significant increase (p < 0.05) in the number of leucocytes relative to control. All fish in the vitamin-supplemented treatments, except 500 mg AA kg- 1, had high total protein values compared to control. Fish treated with 800 or 1200 mg α-T kg- 1 also showed increases in plasma glucose concentrations. Our results suggest that 800 and 1200 mg AA kg- 1 are probably the most suitable concentrations for pirarucu diets, although high vitamin E diets are not necessary for quantitative leucocyte increases for this species. © 2006 Elsevier Inc. All rights reserved.